Efeito de soluções higienizadoras na estabilidade de cor e rugosidade de resinas acrílicas para base de dentadura - Nora, Bárbara Dala (2016)
The aim of the study was to evaluate the effect of cleaning substances in color stability and roughness of acrylic resins to base definitive or provisional dentures polymerized by different methods. The factors evaluated were the type of acrylic resin (autopolymerized, heat-polymerized or microwave-polymerized), immersion media (alkaline peroxide, 0,5% sodium hypochlorite or artificial saliva as control) and time. Seventy-two disc-shaped specimens (8mmx2mm) were prepared (n = 8) and divided according to the experimental design. To determine color change (ΔE00) was used CIEDE2000 equation. The Ra parameter was used to determine the surface roughness of the samples. Baseline measurements were performed 24 hours after hydration (T0) and then the cps were subjected to 20 minutes daily immersions in media. New readings were performed in 30 (T1), 60 (T2) and 90 days (T3). Data were submitted to Analysis of Variance Test for Repeated Measures (Two-way ANOVA) followed by Tukey s Test (p <0,05). Significant effect was found over time, especially in color values (T2 and T3) and roughness for the autopolymerized resin (T3), which behaved worse. The solutions influenced color and roughness. Color stability and roughness were modified by means of immersion and varied depending on the type of polymerization, however the protocol of 20 minutes of immersion in cleaning solutions proved to be safe within the evaluated period for heat-polymerized and microwave-polymerized resin.